2021
DOI: 10.3389/fnsyn.2021.796498
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Organization at the Synapse: Segregation of Distinct Forms of Neurotransmission

Abstract: Synapses maintain synchronous, asynchronous, and spontaneous modes of neurotransmission through distinct molecular and biochemical pathways. Traditionally a single synapse was assumed to have a homogeneous organization of molecular components both at the active zone and post-synaptically. However, recent advancements in experimental tools and the further elucidation of the physiological significance of distinct forms of release have challenged this notion. In comparison to rapid evoked release, the physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 84 publications
0
20
0
Order By: Relevance
“…Extensive work at excitatory synapses via the application of use-dependent drugs and optical imaging have demonstrated the segregation of spontaneous and evoked neurotransmission (Atasoy et al, 2008;Melom et al, 2013;Peled et al, 2014;Reese and Kavalali, 2016;Sara et al, 2011). The distinct functional roles of evoked and spontaneous release at excitatory synapses provides a rationale for robust segregation maintained by prominent nano-organization within single active zones that link pre-and postsynaptic compartments (Biederer et al, 2017;Guzikowski and Kavalali, 2021;Maschi and Klyachko, 2017;Tang et al, 2016). However, due to the unique structure and function of inhibitory synapses, the same properties cannot be assumed for inhibitory neurotransmission but should be thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive work at excitatory synapses via the application of use-dependent drugs and optical imaging have demonstrated the segregation of spontaneous and evoked neurotransmission (Atasoy et al, 2008;Melom et al, 2013;Peled et al, 2014;Reese and Kavalali, 2016;Sara et al, 2011). The distinct functional roles of evoked and spontaneous release at excitatory synapses provides a rationale for robust segregation maintained by prominent nano-organization within single active zones that link pre-and postsynaptic compartments (Biederer et al, 2017;Guzikowski and Kavalali, 2021;Maschi and Klyachko, 2017;Tang et al, 2016). However, due to the unique structure and function of inhibitory synapses, the same properties cannot be assumed for inhibitory neurotransmission but should be thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past seven decades, our picture of synaptic neurotransmission has expanded to include both action potentialdependent release and spontaneous release, both of which have distinct physiological roles (Andreae and Burrone, 2018;Gonzalez-Islas et al, 2018;Kavalali, 2018). Extensive work has been conducted at the excitatory synaptic terminal delineating a precise transsynaptic alignment of molecular nanocolumns that drives the segregation of evoked and spontaneous release (Biederer et al, 2017;Guzikowski and Kavalali, 2021;Maschi and Klyachko, 2017;Ramsey et al, 2021;Tang et al, 2016). However, it remains unclear whether a similar nanostructure applies to inhibitory synapses as well.…”
Section: Introductionmentioning
confidence: 99%
“…Taking this hypothesis into account, it can be proposed that natural palmitoylation of STX1A’s TMD and forced palmitoylation of STX3A’s TMD might increase the number of SVs that more easily overcome the energy barrier for membrane merger. Alternatively, it is also proposed that spontaneous and Ca 2+ -evoked release are mechanistically and spatially distinguished (Guzikowski and Kavalali, 2021; Kaeser and Regehr, 2014; Kavalali, 2015) and thus it can be suggested that palmitoylation of STX1A’s TMD drives it to the release sites allocated for spontaneous vesicle fusion. This implies a dynamic regulation of STX1A palmitoylation based on needs of spontaneous release.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is also proposed that spontaneous and Ca 2+ -evoked release are mechanistically and spatially distinguished (Guzikowski and Kavalali, 2021;Kaeser and Regehr, 2014;Kavalali, 2015) and thus it can be suggested that palmitoylation of STX1A's TMD drives it to the release sites allocated for spontaneous vesicle fusion. This implies a dynamic regulation of STX1A palmitoylation based on needs of spontaneous release.…”
Section: Palmitoylation Of Stx1a's Tmd Potentially Reduces the Energy...mentioning
confidence: 99%
“…Synaptic vesicles fuse to the plasma membrane within the presynaptic bouton in a domain called the active zone, and the intricate molecular architecture within the active zone determines the dynamics of the neurotransmitter release (Guzikowski & Kavalali, 2021). Vesicle fusion is driven by calcium influx and binding to the calcium sensor synaptotagmin on the synaptic vesicle (Geppert et al, 1994; Littleton, Stern, Schulze, Perin, & Bellen, 1993; Ward, Weber, & Chapman, 2004).…”
Section: Introductionmentioning
confidence: 99%